PENGEMBANGAN VARIASI MENGAJAR BAGI GURU BIDANG STUDI AQIDAH AKHLAK MADRASAH DAARUSSALAM BENGKALIS - Sariah Sariah (Sosial Budaya, 2011)
Functioning National education build ability and forms character and nation civilization that gets dignity in order to smarten up nation life that aims for its amends participant potency is taught that becomes devout man and get godfearing to God That Esa Mighty, get noble behavior, healthy bookish, adroit creative, independent and as citizen which democratic and bertangung answers. Therefore akhlaq's believe education have momentous role, since this studi's area form unwavering confidence and forms nation child moral that firm, therefore respondent teacher for can teach and teaching by various variation and rejoicing so not palls. Of temporary watch at MA Daarussalam Duku's Causeway learns studi's area akhlaq's believe haven't utilized variation teaches optimal one. This observational thus at focuses on Variation Development Teaches on Studi's Area Akhlaq Madrasah Aliyah Daarussalam's Believe Duku's Causeway. There is even that as research question is: 1. How is development var. teach studi's area teacher Behavior Believe at Madrasah Aliyah Daarussalam Bengkalis. Population in observational is learn Behavior Believe. 2. Factor what do regard variation teaches studi's area teacher Behavior Believe at Madrasah Aliyah Daarussalam Bengkalis. Population in observational is learn Behavior Believe. Instrument who is utilized for downloading is Observation, interview and documentation. Result observationaling to point out that Variation Development Teaches To Learn Behavior Believe comes under is still less variatif. It is evident of yielding prosentasi's extrapolation they foots up Answer which is “ YES ” = 55 % and answers “ Not ” = 45 %. Therefore 55 % lies among range 49 % 75 % (Variation Teaches adverse).